A NATIONAL SURVEY TO IDENTIFY HOW DISPLACEMENT VALUE INFORMATION IS USED AND PRESENTED TO CLINICAL STAFF IN NHS HOSPITALS. Issue 9 (17th August 2016) - Christiansen, Nanna; Kehk, Zinab; Keeling, Susan; Dean, Bryony
Abstract : Aim: The use of displacement values (DVs) when preparing intravenous (IV) medication for children enables accurate doses to be given1 and is assumed to be common paediatric practice. This survey aimed to assess views of UK paediatric pharmacists on DVs in practice to explore: ▸ How prevalent is DV use in the paediatric hospital setting ▸ Which type of IV administration guidelines were being used ▸ Which form of DV presentation is perceived to be most practical ▸ Which method of calculation is preferred Method: A national cross-sectional survey study was undertaken. The questionnaire comprised of 13 closed and open questions as well as samples of how DVs are currently displayed on the Medusa Injectable Medicines Guide2 . After piloting the questionnaire the survey was sent to 365 paediatric pharmacists across 120 UK hospitals utilising Qualtrics Survey Software. Results: Fifty-five completed questionnaires covering 52 (43%) United Kingdom (UK) hospital trusts were received. Of 55 respondents, 52 (95%) reported the clinical significance of DVs in paediatric care. This was reflected in the fact that all local guides provided information on DVs. The majority (32;59%) used locally produced guides, while 15 (27%) of respondents used Medusa as a resource. All respondents commented on methods of presentation and calculation of DV information. Of four methods presented, the method involving presentation of reconstitution information in a brand-specific table was ranked as most practical (46;84% respondents). This method was viewed as being clear and concise. Respondents also expressed the importance of having this tabulated method visually embedded in the monograph to allow easy access to information on the wards. This concurs with suggested information presentation to aid error reduction in the literature.3 National standardisation of DV information was viewed as 'very useful' or 'preferred' by 52 (95%) of respondents; reasons for this preference were risk reduction due to errors or misinterpretation. Conclusion: The use of DVs in paediatrics is commonplace in the UK; this is reflected in local IV guides used by the majority of centres. Improving visual presentation of DVs is important and tabulated expression of DVs is preferred by pharmacists and a national standard presentation of DVs is encouraged. The results from the survey will inform the monograph layout for the Medusa. Prior to implementation nurse feedback should also be sought.